Conditioning effects on thermal and dynamic mechanical properties of injection moulded glass fibre reinforced polyamide 6,6 composites - Aziz, H.; Abdul Rahman, N. (2011)
Polymer composites of polyamide 6,6 reinforced with short glass fiber were prepared by injection molding, conditioned under dry, 50% relative humidity (RH) and wet. Molded specimens were analyzed by thermogravimetric analyzer (TGA), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). TGA results revealed that glass fiber loading in PA 6,6 improve the thermal stability of the composites by an increase in Tonset and T50% as well as DTp values. DSC analysis revealed that the incorporation of glass fiber and moisture into the PA 6,6 matrix resulted in a remarkable decrease in the degree of crystallinity. However, the melting and crystallization temperatures of the composites are not significantly altered. DMA results revealed the glass transition temperatures are sensitive to moisture absorption and their values move to a lower temperature upon exposure to moisture.